KEANEKARAGAMAN FUNGI MIKORIZA ARBUSKULA PADA HUTAN TRI DHARMA UNIVERSITAS SUMATERA UTARA - Alan Syahputra Simamora; Delvian Delvian; Deni Elfiati (Peronema Forestry Science Journal, 2015)
The goal of this research is to know the diversity of Arbuscular Mycorrhizal Fungi on Tri Dharma Forest University of North Sumatra. The samples of soil and roots of plants taken from the land of Tri Dharma Forest University of North Sumatra. This research use soil separating method to obtain spores and root coloring method to find out root colonization.The results show that an increase in the average density of spores from the field on the results of trapping, for the percentage of Arbuscular Mycorrhizal Fungi colonization in the roots of plants at 56,5% include grade 4 or high categories. Found 2 genus, namely Genus Acaulospora and Genus Glomus. Of the field found as many as 20 types of spores by average spore density 27 spores/50 g soil and trapping results are found as many as 26 types of spores by average spore density 102 spores/50 g soil.Key words: Mycorrhizal Fungi Fungi, Tri Dharma Forest